Examining social vulnerability to flood of affordable housing communities in Nanjing, China: Building long-term disaster resilience of low-income communities. (August 2021) - Chen, Yi; Liu, Tao; Ge, Yi; Xia, Song; Yuan, Yu; Li, Wanrong; Xu, Haoyuan
Highlights: Social vulnerability to flood is conceptualized and assessed from three dimensions of exposure, sensitivity and adaptability. Individual-level survey data were collected to explore the influencing factors of social vulnerability. Affordable housing communities far from the city center are more likely to have a low level of flood vulnerability. Results suggest a variety of approaches that can be adopted to reduce the social vulnerability to flood. Abstract: In the context of climate change and rapid urbanization, urban floods disasters occur frequently across the globe, and social vulnerability has become an important theoretical perspective for understanding the occurrence and response of flooding disasters. This paper takes Nanjing as an example to investigate flooding disasters and social vulnerability in development countries. It develops an analysis framework and evaluation index system of social vulnerability from three dimensions of exposure, sensitivity and adaptability. Ten typical affordable housing communities were selected and individual-level survey data were collected to explore the influencing factors of social vulnerability. The results show that social vulnerability is simultaneously affected by exposure, sensitivity and adaptability. Communities with new construction ages and good built environments usually have lower levels of risk exposure. Those with residents having higher levels of education and social capital have lower sensitivity. The government's emergency operations and residents' response capabilities can both significantly improve the adaptability of communities to floods.